2019
DOI: 10.5539/jas.v11n18p88
|View full text |Cite
|
Sign up to set email alerts
|

Control of Anticarsia gemmatalis (Hübner: 1818) (Lepidoptera: Erebidae) and Chrysodeixis includens (Walker: 1858) (Lepidoptera: Noctuidae) Through Insecticides Applied to Soybean Seeds

Abstract: Brazil is the second largest producer of soybeans in the world, with the state of Mato Grosso having the highest production in the country. The soybean crop faces major phytosanitary difficulties throughout its cultivation, as is the case of pest incidence, especially the defoliating caterpillars that can cause intense defoliation of soybean and affect its productivity. Thus, the objective of this work was to evaluate the effect of different insecticides when applied in soybean seed treatment, on leaf consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…Results similar to those obtained, but with A. gemmatalis in this study were demonstrated by Vieira et al (2019) which state that in a trial of controlling the track, the last evaluation of leaf consumption and mortality made with plants soybean (35 DAE), the treatment fipronil, had the highest foliar consumption and the lowest mortality of caterpillars, while the mixture of cyantraniliprole + thiamethoxam had the lowest leaf consumption.…”
Section: Spodoptera Frugiperdasupporting
confidence: 86%
“…Results similar to those obtained, but with A. gemmatalis in this study were demonstrated by Vieira et al (2019) which state that in a trial of controlling the track, the last evaluation of leaf consumption and mortality made with plants soybean (35 DAE), the treatment fipronil, had the highest foliar consumption and the lowest mortality of caterpillars, while the mixture of cyantraniliprole + thiamethoxam had the lowest leaf consumption.…”
Section: Spodoptera Frugiperdasupporting
confidence: 86%
“…Currently, several control methods, including synthetic insecticides, Bt crops, biological control and cultural practices have been adopted in the integrated pest management directed against the insect pests H. armigera, A. gemmatalis, S. cosmioides, C. includes, and D. saccharalis to achieve more effective crop protection (Bortolotto et al 2015;Blanco et al 2016;Mascarin et al 2018;Vieira et al 2019). The economic, environmental and social benefits offered by the insect-resistant Bt crops and Bt bioinsecticides have driven increasing adoption of these strategies for controlling a wide variety of insect pests (Lacey et al 2015;Dively et al 2018;Romeis et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Among the most essential groups of pests that attack soybean crops are caterpillars (Lepidoptera larvae). These pests damage plants by defoliating and attacking stems, flowers, pods, and grains [7,13]. In the past, the most abundant Lepidoptera species in soybean crops in the Neotropics was Anticarsia gemmatalis (Hübner) (Noctuidae).…”
Section: Introductionmentioning
confidence: 99%